Determining the Predictive Contribution of Addiction Readiness Based on Identity Styles with the Mediation of Self-Differentiation and Social Problem-Solving in Prisoners of Isfahan Province - Kazemi Zahrani, Hamid; Ebrahimi Alavijeh, Elahe (KMAN Counseling & Psychology Nexus, 2025)
The present study aimed to determine the predictive contribution of addiction readiness based on identity styles with the mediation of self-differentiation and social problem-solving. The statistical population of this study included all male prisoners in the central prison of Isfahan Province in 2019. From this population, 120 individuals were selected using the convenience sampling method. Four standardized questionnaires were used in this study: the Addiction Readiness Questionnaire, the Identity Style Questionnaire, the Self-Differentiation Scale, and the Social Problem-Solving Inventory. The results of hypothesis testing indicated a significant direct relationship between identity styles and addiction readiness. Furthermore, in the relationship between the informational identity orientation and addiction readiness, the variable of social problem-solving played a mediating role. However, in the relationship between other identity styles (normative identity style, diffuse-avoidant identity style, and commitment) and addiction readiness, the variables of self-differentiation and social problem-solving did not have a mediating role (p > .05). Based on the study’s findings, it is recommended that family education centers, prisons, and mass media raise individuals’ awareness regarding the importance of achieving a successful identity. Additionally, at-risk individuals should be encouraged to actively process information, engage with identity-related issues, and participate in problem-solving activities. Training programs should also be implemented to enhance these factors.